Lowering propionic acid levels by regulating gut microbiota with ursodeoxycholic acid appears to regress autism symptoms: an animal study - Karakaş, Levent; Solmaz, Volkan; Bagcioglu, Erman; Özkul, Bahattin; Sogut, Ibrahim; Uyanikgil, Yigit; Erbas, Oytun (My University, 2023)
Aims: Patients with autism have altered gut microbiata, including higher frequency of bacteroidetes and clostridiales that produce of propionic acid (PPA) –a compound that is established as an autism-inducing agent. We hypothesized that lowering the PPA levels by regulating gut microbiata with ursodeoxycholic acid (UDCA) can regress the autism symptoms. The aim of this study is to examine the potential ameliorating effects of UDCA on a PPA-induced rat model of autism. Methods: Thirty male Wistar albino rats were divided into three groups: controls, PPA-induced (5 days of intraperitoneal 250 mg/kg/day dosage) autism model receiving oral saline, and PPA-induced autism model receiving oral UDCA (100 mg/kg/day). Oral treatments were applied for 15 days. At the end of the 15th day, all rats underwent behavioral tests and MR spectroscopy. At the end of the study, all animals were sacrificed and brain tissue / blood samples were collected for histopathological and biochemical analyses. Results: Sociability test, open field test and passive avoidance learning tests were impaired, similar to the autism behavioral pattern, in PPA recipients; however, results were closer to normal patterns in the PPA+UDCA group. Biochemically, MDA, TNF-alpha, IL-2, IL-17, NF-kB, lactate, NGF and NRF2 levels in brain tissues showed significant differences between controls and the PPA+Saline group, and between the PPA+Saline group and the PPA+UDCA group (p< 0.05, for all). Histopathology showed that PPA injection caused increased glial activity, neural body degeneration, decreased neural count and dysmorphic changes in hippocampal and cerebellar tissues (p<0.01, for all). UDCA treatment significantly ameliorated these changes. Conclusion: UDCA administration has ameliorating effects on PPA-induced autism-like behavioral, biochemical and histopathological changes in rats.
Keywords: Autism, Ursodeoxycholic Acid, Propionic Acid, Gut Microbiota